Online and Offline Students’ Presentation in Thesis Proposal: Challenges and Solution - Nani Hizriani; Khairatunnisa Khairatunnisa; Hidayah Nor; Ciptro Handrianto (RIRAI Publisher, 2022)
Thesis proposal seminar is one of requirements for English Department students to process their thesis. Students should present their thesis proposal which provide information about their research. The presentation covers research topic, theoretical framework, and chosen methodology. This research focuses on the challenges of thesis proposal seminar both online and offline. This also identifies students’ solutions for making a good presentation. This is a descriptive qualitative research since it is used to describe the challenges of students and find out the solutions by questionnaire and in-depth interview. The subjects of this research are 35 students who have taken research and seminar subjects and has presented thesis proposal seminar offline and online in January–May. The findings show that students faced some challenges during thesis proposal seminar related to seminar preparation, topic’s mastery, students’ confidence and technical issues. To make a good presentation, students need to understand their research topic and research methodology well. They also need to plan their presentation by doing a lot of practices and having good preparation. These solutions necessarily encourage students’ confidence and motivation to do presentation effectively.